2007
DOI: 10.1093/ije/dym220
|View full text |Cite
|
Sign up to set email alerts
|

Back pain, a communicable disease?

Abstract: Various processes may have contributed to the observed changes. Our hypothesis is corroborated by experimental research showing that BP-related beliefs, attitudes and behaviour could positively be influenced by media campaigns and by insights from another recent epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…5 Some argue that episodic LBP is a universal part of human experience. 6,7 Half of the adult population in the UK (49%) report LBP lasting at least 24 hours in a one year period. 5 The 2010 Global Burden of Disease study identified LBP as the leading cause of years lived with disability internationally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Some argue that episodic LBP is a universal part of human experience. 6,7 Half of the adult population in the UK (49%) report LBP lasting at least 24 hours in a one year period. 5 The 2010 Global Burden of Disease study identified LBP as the leading cause of years lived with disability internationally.…”
mentioning
confidence: 99%
“…The scoring for each item ranges from 0 (less than 1 day per week) to 3 (5 to 7 days per week). The scoring for items 2, 6,7,12, 14,16,18,20,21 and 23 is reversed.MZDI score = sum of all items.The range of the score is from 0 to 69 where higher score indicates more depressed. …”
mentioning
confidence: 99%
“…Trotz der Erleichterung der Arbeitsplatzbedingungen in den Industrienationen in den letzten Jahrzehnten ist die Prävalenz von Rückenschmerzen nicht zurückgegan-gen [25]. Vergleichende Untersuchungen in verschiedenen Ländern zeigen deutlich, dass Rückenschmerzen überall auf der Welt häufig sind.…”
Section: Indikator Kreuzschmerzarbeitsunfähigkeitunclassified
“…Episodes of acute low back pain are a universal human experience (1). Usually, this is a benign, selflimiting disorder that does not require professional advice or specific treatment (2).…”
Section: Martin Underwoodmentioning
confidence: 99%